Suicide Bombers: Examining Why They Do What They Do - Agara , Tunde; Ikhanafe, Imokhai Philip (Kashere Journal of Politics and International Relations, 2025)
This study explores the motivations and structural underpinnings of suicide bombers, examining why individuals choose to participate in acts of self-sacrificial violence. Through a detailed analysis, the research dissects suicide terrorism as both a psychological commitment and a calculated strategy leveraged by extremist organizations to inflict fear and attract attention. Key factors shaping this phenomenon include ideological devotion, social alienation, and personal grievances, all of which can render individuals more susceptible to recruitment by terrorist groups. The study outlines the roles of various actors—The Founders, The Evangelists, The Prisoners, and The Aristocrats—who collectively fuel the operational and ideological machinery of suicide terrorism. This network works synergistically to recruit, indoctrinate, and sustain operations that keep suicide terrorism a viable tactic within extremist groups. Special attention is given to the evolving role of women in these acts, with analysis on how gender dynamics have led to their increased involvement as suicide bombers. Women are often viewed as less suspicious and more mobile in restricted areas, making them valuable assets in executing these attacks. Additionally, cultural narratives surrounding martyrdom are used to shape perceptions of sacrifice and honor among female recruits, reinforcing their commitment to the cause. The findings suggest that effective counterterrorism efforts must consider the psychological and social dimensions of suicide terrorism. Addressing underlying issues such as socio-economic disparities, ideological indoctrination, and the glorification of martyrdom may help weaken the appeal of extremist recruitment.